Trabeculotomy ab interno with Trabectome as surgical management for systemic fluoroquinolone-induced pigmentary glaucoma: A case report. Issue 43 (October 2017) - Den Beste, Kyle A.; Okeke, Constance
Abstract: Rationale: Bilateral acute iris transillumination (BAIT) is a poorly-understood ocular syndrome in which patients present with acute iridocyclitis and pigmentary dispersion with or without ocular hypertension. The etiology of the disease remains unknown, though recent reports suggest an antecedent upper respiratory tract infection or systemic antibiotic administration may trigger the clinical syndrome. Patient concerns: A 55-year-old female was referred for a second opinion regarding her bilateral ocular pain, photophobia, and ocular hypertension. Her medical history was notable for a diagnosis of pneumonia managed with oral moxifloxacin several weeks prior to her initial presentation. Diagnoses: Visual acuity was 20/40 with an intraocular pressure (IOP) of 30 mmHg in the affected eye despite maximal tolerated medical therapy. The patient had severe bilateral iris transillumination defects with posterior synechiae formation and 3+ pigment with rare cell in the anterior chamber. This constellation of findings was consistent with a diagnosis of BAIT. Interventions: A peripheral iridotomy was placed, which mildly relieved the iris bowing, but did not affect the IOP or inflammatory reaction. The patient then underwent cataract extraction with posterior synechiolysis and ab interno trabeculotomy of the left eye with the Trabectome. Outcomes: The patient's IOP on the first post-operative day was 13 mmHg, and anterior chamber inflammation was noted to be significantly reduced at post-operative week 2. The patient was recently seen at a 1-year post-operative visit and her IOP remains in the low teens on a low-dose combination topical agent. Lessons: Ophthalmologists should remain aware of the association between systemic fluoroquinolones and acute pigmentary dispersion that can progress to glaucoma. The Trabectome remains a viable option for management of pigmentary and uveitic glaucoma resistant to medical treatment.